2000
DOI: 10.1074/jbc.275.6.3991
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific Transcriptional Regulation of theslowpoke Ca2+-activated K+Channel Gene

Abstract: Transcriptional regulation of the Drosophila slowpoke calcium-activated potassium channel gene is complex. To date, five transcriptional promoters have been identified, which are responsible for slowpoke expression in neurons, midgut cells, tracheal cells, and muscle fibers. The slowpoke promoter called Promoter C2 is active in muscles and tracheal cells. To identify sequences that activate Promoter C2 in specific cell types, we introduced small deletions into the slowpoke transcriptional control region. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Recently, the cardiac muscle-specific channel, hyperpolarization-activated cyclic nucleotide-gated potassium channel 4, was shown to be a direct target of the MEF2 (myocyte-specific, enhancer-binding factor 2) transcription factor (56). In Drosophila, the Kcnma1 gene (slowpoke) is controlled by multiple promoters, including one directing expression of this channel in muscle fibers and tracheal cells through sequences containing MEF2 and E-box binding sites (57). The orthologous mouse Kcnma1 gene is also under the control of several promoters that contain E-boxes, MEF2 sites, and putative CArG boxes (58), some of which are conserved in the human ortholog (59).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cardiac muscle-specific channel, hyperpolarization-activated cyclic nucleotide-gated potassium channel 4, was shown to be a direct target of the MEF2 (myocyte-specific, enhancer-binding factor 2) transcription factor (56). In Drosophila, the Kcnma1 gene (slowpoke) is controlled by multiple promoters, including one directing expression of this channel in muscle fibers and tracheal cells through sequences containing MEF2 and E-box binding sites (57). The orthologous mouse Kcnma1 gene is also under the control of several promoters that contain E-boxes, MEF2 sites, and putative CArG boxes (58), some of which are conserved in the human ortholog (59).…”
Section: Discussionmentioning
confidence: 99%
“…Both 55b and 6b are non–promoter-containing DNA sequences that were originally identified because of their conservation between two Drosophila species [19,63]. Conservation alone is a strong indicator that these sequences have important roles in the regulation of the slo gene.…”
Section: Discussionmentioning
confidence: 99%
“…(A) Alignment of the 55b box [63] and (B) the 6b box [19] across eight Drosophila species. Areas of highest identity (80%) are boxed, and black bars below the line denote transcription factor binding motifs that are conserved in these species.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances these multiple promoters behave differentially under different cellular conditions. For example, Drosophila Slo gene (dSlo) has multiple promoters whose expression is differentially regulated in muscle or the central nervous system (16,18). However, the role of multiple TSSs or exactly how they are regulated in mammals is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Answering this question had as a prerequisite the establishment of the promoter(s) architecture. In this regard, studies of the Drosophila homolog gene, slowpoke (dSlo), have shown that this gene contains multiple promoters that regulate dSlo expression in a tissue-specifie (15)(16)(17)(18) and developmental stage-specific manner (19). However, no studies * This work was supported by National Institutes of Health Grants HL54970…”
mentioning
confidence: 99%